Fatigue Durability Analysis of Collecting Rapping System in Electrostatic Precipitators under Impact Loading. (12th January 2014) - Neyestanak, Ali Akbar Lotfi; Adib Nazari, Saeed; Imam, Ali; Aghanajafi, Cyrus
Abstract : Due to the importance of collecting rapping system in electrostatic precipitators (ESP) and controlling the relevant damage under impact loading, fatigue durability of this system is analyzed in the present study based on the numerical and experimental results considering fatigue damage growth and vibration acceleration in the collecting system because of the successive impact of rapping hammers. By microscopic examination of the fracture surface of rapping hammer, beach marks obviously show typical fatigue failure in the rapping hammer arm. In addition, the microscopic examination of the cross section of the collecting plates indicates the corrosion voids which cause crack and eventually fatigue failure. The finite element method is applied to determine both the stress and concentration positions of dynamic stress on the rapping system under impact loading. The paper results can be utilized in system optimization and new material selection for the system by evaluating rapping system durability.